Chemical processing of three-dimensional graphene networks on transparent conducting electrodes for depleted-heterojunction quantum dot solar cells. Issue 2 (30th October 2015) - Tavakoli, Mohammad Mahdi; Simchi, Abdolreza; Fan, Zhiyong; Aashuri, Hossein
Abstract : The improvement of device performance by using a 3DGN structure as a fast extraction layer for electrons is shown. Abstract : We present a novel chemical procedure to prepare three-dimensional graphene networks (3DGNs) as a transparent conductive film to enhance the photovoltaic performance of PbS quantum-dot (QD) solar cells. It is shown that 3DGN electrodes enhance electron extraction, yielding a 30% improvement in performance compared with the conventional device.